2018
DOI: 10.1007/s40203-018-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

Design of novel amyloid β aggregation inhibitors using QSAR, pharmacophore modeling, molecular docking and ADME prediction

Abstract: The inhibition of abnormal amyloid β (Aβ) aggregation has been regarded as a good target to control Alzheimer's disease. The present study adopted 2D-QSAR, HQSAR and 3D QSAR (CoMFA & CoMSIA) modeling approaches to identify the structural and physicochemical requirements for the potential Aβ aggregation inhibition. A structure-based molecular docking technique is utilized to approve the features that are obtained from the ligand-based techniques on 30 curcumin derivatives. The combined outputs were then used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…As expected, the oral bioavailability decreases with increasing molecular weight and increases with the deacetylation degree. PreADMET predictions concerning the percent of the human intestinal absorption (HIA, Supplementary Table 2) reveal a mean absorbance (20%<HIA<70%) (Aswathy et al, 2018) for the monomeric units, the highest value (60.25%) being registered for the GlcN oligomer. Chito-oligomers containing two monomeric units reflect a poor absorption (HIA<20%) and the other COs do not reflect intestinal absorption (HIA = 0).…”
Section: Resultsmentioning
confidence: 99%
“…As expected, the oral bioavailability decreases with increasing molecular weight and increases with the deacetylation degree. PreADMET predictions concerning the percent of the human intestinal absorption (HIA, Supplementary Table 2) reveal a mean absorbance (20%<HIA<70%) (Aswathy et al, 2018) for the monomeric units, the highest value (60.25%) being registered for the GlcN oligomer. Chito-oligomers containing two monomeric units reflect a poor absorption (HIA<20%) and the other COs do not reflect intestinal absorption (HIA = 0).…”
Section: Resultsmentioning
confidence: 99%
“…In the same study, ligand-based drug design led to the identification of a lead compound that has similar anti-Aβ aggregation properties as the peptide. The structural and physicochemical requirements for the potential Aβ aggregation inhibition were investigated on a set of 30 curcumin derivatives using docking, 2D-QSAR, HQSAR, and 3D QSAR [111]. The Aβ aggregation inhibitory activities of newly design molecules were predicted through inverse QSAR, and further screened using machine learning and toxicity prediction models to finally identify six lead compounds.…”
Section: Cadd For the Development Of Anti-aβ Aggregation Inhibitorsmentioning
confidence: 99%
“…Quantitative regression models suggest that the use of canvas descriptors can achieve better statistical accuracy similar to 3D field-based techniques that often require molecular alignment of diverse chemical scaffolds in one universal chemical space. Aswathy et al (2018) identified the structural and physicochemical requirements for the potential inhibition of Aβ aggregation, and molecular docking analyses of the representative inhibitors were performed to determine the binding modes of inhibitors at the active site of the protein. They used a random forest based model to test the activity of novel chemical entities and to screen the newly designed molecules.…”
Section: Machine Learning Techniques and Its Application On Alzheimermentioning
confidence: 99%